Organisaatioiden eettinen infrastruktuuri konfliktien johtamisen suunnannäyttäjänä - Kantola, Jenni; Hietanen-Kunwald, Petra; Doty, Anisa (Hallinnon tutkimuksen seura, 2023)
Ethical infrastructure of organizations as a guide for conflict management Unethical behavior at the workplace may have a negative impact on workers´ job satisfaction, engagement, and overall wellbeing. However, organizations have different strategies and orientations to managing and sustaining an ethical environment. In this qualitative study we explore what contributes to individuals´ experience of successful conflict management. We study this from the perspective of ethical infrastructure, that is a set of formal and informal systems that build ethical culture in organizations. We conducted nine in-depth interviews and used the first two phases of Appreciative Inquiry (AI) (define and dream) to identify and envision good practice. The study identified constructive practice, collective agency, communication, emotional skills, and a working culture based on dialogue as factors supporting future workplaces in conflict resolution. The study highlights the need to understand conflict management as being dependent on, and in interaction with other elements
Keywords: conflict management; ethical infrastructure; appreciative inquiry; Gioai method; fi=Henkilöstöjohtaminen|en=Human Resource Management|